Molecular analysis of the 16S rRNA Gene for the identification of Shigella sp. in freshwater snail (Faunus ater) - Masda Admi; Veronika Puja Koswari; Winaruddin Winaruddin; Wahyu Eka Sari; Teuku Zahrial Helmi; Azhari Azhari; Faisal Jamin (Arwana: Jurnal Ilmiah Program Studi Perairan, 2025)
Freshwater snails (Faunus ater) live in shallow, muddy, and sandy waters and obtain their food through a filter-feeding mechanism. These conditions make freshwater snails potentially exposed to various contaminants within their bodies, such as heavy metals and bacteria. This study aims to identify the presence of Shigella sp. in Faunus ater using 16S rRNA gene analysis. The research method was conducted through observational and laboratory exploration using a modified Carter method and 16S rRNA gene analysis. Phenotypic observations showed bacterial growth in Brain Heart Infusion Broth (BHIB) media, producing clear, round-shaped colonies on Salmonella Shigella Agar (SSA) media, and were classified as Gram-negative, short rod-shaped bacteria. The 16S rRNA gene analysis results showed that the isolate had a 98.35% similarity to Shigella flexneri strain FDAARGOS_692. It can be concluded that the molecular analysis of the 16S rRNA gene of the bacterial isolate from the freshwater snail indicates that the bacteria belong to the genus Shigella and are similar to Shigella flexneri strain FDAARGOS_692.